Application of generalized comb wavelet functions for angiogram image segmentation - Полякова, Марина Вячеславовна; Ищенко, Алеся Владимировна; Емец, Юрий Владимирович (Technology audit and production reserves, 2013)
The existing methods of angiograms processing do not provide the required speed and quality of segmentation, which determines the accuracy of diagnostic solutions. Therefore, to reduce the angiograms processing time a method has been developed for segmentation of the vessels illustrations on the 3098pangiograms, and analyze the result of segmentation by means of conversion with the generalized comb wavelet function at the vessels localization and the replacement of several processing levels by the one. The latter is achieved by the fact that the convolution with a generalized comb wavelet function is similar to using a set of bandpass filters. At the phase of segmentation results analysis of the vessels skeleton excretion was increased using morphological processing. The implementation of the developed method has allowed to reduce angiogram images processing time at 43% that is required to combine the diagnostic and therapeutic potential of the angiography method during a single procedure. Thus, the noise resistance characteristics may be changed as follows: the probability of the 1st type error is 1.22 times reduced, and the probability of the 2nd type error 1.14 times increases. As a result of experiments, it was shown that the developed method provides the vessels localization quality required for accurate singling out of the diagnostic parameters of heart disorders, which improves the accuracy of heart diseases diagnosing.